Application of operations research techniques in planning forestry and forest industries development in Malaysia - Hadi, Yusuf; Manikam, Doraisingam; Hashim, Ismail (1985)
Past application and the potential of Operations Research techniques in planning forestry and forest industries development in Malaysia are discussed. To date, three simulation models have been developed to calculate timber production and to assess the impact of various harvesting strategies on selected socio-economic parameters. The simulations technique was also employed to model the growth of forest stands in Pahang and Sarawak. Linear programming models have been developed to calculate timber supply, and to allocate logs to processing mills and distribute the products to consumer points. A critical path method was utilized to schedule logging operations. There is a great potential for the application of these techniques in Malaysia. Their potential application spans the whole spectrum from modelling forest growth, through timber management planning, forest harvesting, allocating logs to mills and improving timber conversion processes, to marketing the final products.